PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN GUDEG LUMINTU JEMBER - Yuliani, Dien; Suharyatik, Suharyatik; Aisyah, Shierley; Tjahjono, Tri; Qomariah, Nurul (Fakultas Ekonomi dan Bisnis, 2022)
The increasingly fierce competition in the culinary business means that every business actor must be able to differentiate between one business and another so that it has advantages that can attract the attention of consumers. Business actors must ensure consumer satisfaction and design appropriate marketing strategies to encourage repeat purchases. Effective marketing is the key to convincing consumers to choose a product. This research aims to analyze the influence of service quality and product quality on Gudeg Lumintu Jember customer loyalty. The population of this research is all Gudeg Lumintu Jember customers with a sample of 75 respondents. Descriptive analysis, validity, reliability, classical assumptions and research hypothesis testing were used to analyze the data. The results of this research are expected to show a significant influence of service quality and product quality on Gudeg Lumintu Jember customer loyalty.